2010
DOI: 10.3109/01676830903207810
|View full text |Cite
|
Sign up to set email alerts
|

The “Mini Tarsal Strip” Lateral Canthopexy for Lower Eyelid Laser-Assisted Blepharoplasty—Indications, Technique and Complications in 614 Cases

Abstract: The aim of this article is to describe the "mini tarsal strip procedure", a form of lateral canthal tendon plication to tighten the lower lid and give a better apposition of the lower eyelid to the globe. We describe this procedure in the context of transconjunctival lower lid blepharoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…LTS is a popular procedure for eyelid shortening and can be used either in entropion or ectropion correction [7, 9]. Although LTS is effective in tightening the eyelid, it is known to have disadvantages such as under correction, webbing, recurrence and disruption of the lateral canthal angle [20, 21]. López-García et al [7] reported recurrence rate of 17.4% after conventional tarsal strip surgery for involutional entropion.…”
Section: Discussionmentioning
confidence: 99%
“…LTS is a popular procedure for eyelid shortening and can be used either in entropion or ectropion correction [7, 9]. Although LTS is effective in tightening the eyelid, it is known to have disadvantages such as under correction, webbing, recurrence and disruption of the lateral canthal angle [20, 21]. López-García et al [7] reported recurrence rate of 17.4% after conventional tarsal strip surgery for involutional entropion.…”
Section: Discussionmentioning
confidence: 99%
“…5 Lateral canthopexy accomplishes horizontal tightening by lateral canthal plication without the need for either lateral canthotomy or inferior cantholysis. This procedure may be performed during external blepharoplasty, lower eyelid retractors may be further divided near the lower border of the tarsus, if their tightness appears to limit the full release of the eyelid.…”
Section: Lateral Canthal Tightening Canthopexymentioning
confidence: 99%
“…Slight dehiscence can be treated with topical and oral antibiotics, but a complete dehiscence needs prompt debridement and repair to avoid lower lid retraction and scarring. Milder eyelid laxity is treated by a form of lateral canthal tendon plication at the time of lower lid blepharoplasty, and dehiscence here is less common and of milder extent, and hence can usually be managed supportively [7]. …”
Section: Complicationsmentioning
confidence: 99%
“…In addition, placement of an upper lid traction suture is important or the skin graft will be ineffective [7–9]. Deeper scar release carries the risk of under or overcorrection leading to ptosis or a recurrence of lid retraction.…”
Section: Complicationsmentioning
confidence: 99%